2011
DOI: 10.3928/15428877-20110125-08
|View full text |Cite
|
Sign up to set email alerts
|

Macular Thinning Associated with Unilateral Optic Nerve Hypoplasia

Abstract: The authors present the case of an 8-year-old boy with a long-term diagnosis of unilateral optic nerve hypoplasia (ONH) of unknown cause in the right eye. Spectral- domain optical coherence tomography (SD-OCT) of the central macula was consistent with hypoplasia greatest in the inner retinal layers, but also involving the outer retinal layers when compared with the unaffected contralateral eye. Although ONH is commonly associated with hypoplasia of the nerve fiber and ganglion cell layers, it can also be assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…Using OCT for quantitative assessment of the optic nerve head, retinal nerve fiber layer, and macular thickness, Srinivasan and colleagues 24 reported a decrease in overall macular thickness in a patient with unilateral ONH; however, specific retinal layers were not studied. Hoang and colleagues 25 reported thinning of the outer retinal layers in the central and inferior macular regions on SD-OCT in an 8-year-old with unilateral ONH, similar to our results. In contrast, Park and colleagues 26 reported the macular OCT analysis of a single case of presumed unilateral ONH and found no statistically significant difference between the outer retinal thickness in the ONH eye and the contralateral normal eye.…”
Section: Discussionsupporting
confidence: 91%
“…Using OCT for quantitative assessment of the optic nerve head, retinal nerve fiber layer, and macular thickness, Srinivasan and colleagues 24 reported a decrease in overall macular thickness in a patient with unilateral ONH; however, specific retinal layers were not studied. Hoang and colleagues 25 reported thinning of the outer retinal layers in the central and inferior macular regions on SD-OCT in an 8-year-old with unilateral ONH, similar to our results. In contrast, Park and colleagues 26 reported the macular OCT analysis of a single case of presumed unilateral ONH and found no statistically significant difference between the outer retinal thickness in the ONH eye and the contralateral normal eye.…”
Section: Discussionsupporting
confidence: 91%
“…ONH results from congenital deficiency of retinal ganglion cells and axons that lead to disorganization of the retinal ganglion cell layer, thinning of RNFL, and a small optic disc. [ 4 ] These results cannot be exactly explained, but they are thought of as a result of any insult to the visual pathway before the completion of development, especially in the early developmental period. [ 1 ] The diagnosis of ONH remains primarily on a clinical basis, but it becomes difficult when the degree of hypoplasia is less severe or even segmental in nature,[ 5 ] because the thinning of RNFL and disc appearance are variable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for quantitative analysis of retinal layers, segmentations were done to three parts, which were RNFL, inner retinal layer (IRL), and ORL; on the basis of internal limiting membrane, posterior boundary of the RNFL, posterior boundary of the outer plexiform layer, and anterior boundary of the cone outer segment tip line. [ 3 4 ] RNFL thickness (RNFLT), IRL thickness (IRLT), and ORL thickness (ORLT) were measured manually using the caliper tool in the device. The Wilcoxon's signed-rank test and t -test were used for the comparison of RNFLT, IRLT, and ORLT; between both eyes.…”
Section: Case Reportmentioning
confidence: 99%
“…A few studies have reported that HRT and/or OCT aid in the diagnosis of segmental CONH . Several case reports have revealed that HRT and/or OCT are valuable tests for diagnosing unilateral CONH, including two cases reported from our group . However, to the best of our knowledge, no research study has been conducted to assess whether these new imaging techniques assist in diagnosis of CONH that is not segmental.…”
Section: Discussionmentioning
confidence: 90%